Sensory Loss in China: Prevalence, Use of Aids, and Impacts on Social Participation - Heine, Chyrisse; Browning, Colette J.; Gong, Cathy Honge (Frontiers in Public Health, 2019)
The number of older adults with vision and/or hearing loss is growing world-wide, including in China, whose population is aging rapidly. Sensory loss impacts on older people's ability to participate in their communities and their quality of life. This study investigates the prevalence of vision loss, hearing loss, and dual sensory loss (combined vision and hearing loss) in an older adult Chinese population and describes the relationships between these sensory losses and demographic factors, use of glasses and hearing aids, unmet needs, and impacts on social participation. The China Health and Retirement Longitudinal Study is a population-based longitudinal survey conducted since 2011. The 2013 dataset for people aged 60 and over was used in this study. Items analyzed included demographic data (age, gender, education, rurality, and SES), self-reported ratings of vision (including legally blind, excellent-poor long, and short distance vision and the use and frequency of wearing glasses), hearing (excellent-poor hearing and the use of hearing aids), dual sensory loss (both poor/fair vision and hearing), and social participation. Of the sample, 80.2% reported poor/fair vision, 64.9% reported poor/fair hearing, and 57.2% had poor/fair vision and hearing. Few respondents (10%) wore glasses regularly and 20.1% wore glasses from time to time. Only 0.8% of respondents wore hearing aids although the proportion with hearing loss was high (64.9%). The proportion of unmet needs for glasses and hearing aids was 54.9 and 63.9%, respectively. Low socio-economic status (SES), poor education, and rurality were significantly associated with the prevalence of poor/fair vision and hearing, the use of glasses and hearing aids and the unmet needs of glasses/hearing aids. Poor/fair vision and/or hearing, and the unmet needs for glasses/hearing aids were significantly and negatively associated with social participation. Sensory loss is a significant health issue for older Chinese people that impacts on their social participation. Training primary care health professionals in identification and rehabilitation approaches is needed as well as increasing the numbers of vision and hearing specialists working in the field. Providing information on sensory loss and the use of aids to older adults will also help improve older adult's quality of life.